A Case of an Abdominal Aortic Dissection in a Hemodynamically Stable Marfan Syndrome Patient Presenting without Pain - Hussein Al-Mohamad; Kara Stout; Taryn Bolling; Ronald Walsh (Case Reports in Cardiology)
Introduction. Marfan syndrome (MFS) is a rare connective tissue disorder attributed to a defect in the fibrillin-1 gene. Aortic aneurysms and dissection are common causes of morbidity and mortality in Marfan syndrome. Case Report. A 43-year-old female with a history of MFS and a 4.0 cm dilated ascending aorta presented to her cardiologist reporting that since a C-section two years prior, the left side of her abdomen painlessly protruded when standing. An outpatient CT scan of the abdomen/pelvis noted a 5.5 cm abdominal aortic dissection, and she was directed to the hospital. Repeat CT scan of the abdomen/pelvis revealed a 5.6 cm dissecting aneurysm of the infrarenal abdominal aorta. The patient was admitted to the ICU and started on a nitroglycerin drip to maintain systolic blood pressure less than 110 mmHg. The patient underwent repair of her abdominal aortic dissection via a retroperitoneal approach, and she tolerated the procedure well. She was started on metoprolol tartrate 12.5 mg BID and aspirin 81 mg postoperatively. She was safely discharged with follow-up care. Conclusion. This case stresses the importance of having a low threshold to obtain imaging in a MFS patient with protruding abdomen, even though the patient may not have pain and be hemodynamically stable.